Frameworks of the relations of the 'Customer Value' for the 'Start-Up' business through 'e-service' in the North of Thailand - Raslapat Suteeca (2018)
© 2017 IEEE. currently, there are several 'Start-Up' businesses in Thailand which could be seen by registered entrepreneurs for more than 90 percent of these businesses and there are more than 60 percent out of all workers who have been hired. This study is aimed to study frameworks of the relations' factors which are going to create a 'Customer Value' by applying a Customer Value Hierarchy Model including infrastructure, social psychology and image building or branding for the Start - Up business services through the e-service to satisfy the customers' satisfaction and to achieve a sustainable business in the North of Thailand.